2012
DOI: 10.1080/13662716.2012.739782
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Innovations, Local Networks and Internationalization

Abstract: This paper investigates the forces correlated with environmental innovations (EIs) introduced by firms in local production systems (LPS). The role of inter-firm network relationships, agglomeration economies and internationalization strategies is jointly analysed for a sample of 555 firms in the EmiliaRomagna (ER) region (North-East Italy). Cooperating with a certain kind of local actors-i.e. suppliers and universities-is the most important EI driver for the investigated firms, along with their training covera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
179
3
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(213 citation statements)
references
References 98 publications
13
179
3
3
Order By: Relevance
“…EIs are more cooperation-intensive than general innovations, that is, eco-innovators rely more on the competences of external partners than other innovators (Cainelli et al, 2012;De Marchi, 2012;Del Río et al, 2015). Thus, collaboration between firms on environmental issues is likely to contribute to green the corporate strategies of firms.…”
Section: Indirect Effects On Ei Through Environmental Strategymentioning
confidence: 99%
“…EIs are more cooperation-intensive than general innovations, that is, eco-innovators rely more on the competences of external partners than other innovators (Cainelli et al, 2012;De Marchi, 2012;Del Río et al, 2015). Thus, collaboration between firms on environmental issues is likely to contribute to green the corporate strategies of firms.…”
Section: Indirect Effects On Ei Through Environmental Strategymentioning
confidence: 99%
“…They found that firms' investments in greener technologies have positive economic results for companies and also for the sector as a whole. The works of Antonioli and Mazzanti (2009) and Cainelli, Mazzanti, and Montresor (2012) are similar. Others authors, using anecdotal evidence or case studies, have found that environmental regulation can motivate firms to innovate (Ghisetti & Rennings, 2014;Porter & Van der Linde, 1995).…”
Section: Determinants Of Eco-innovationmentioning
confidence: 99%
“…The surveyed firms were divided according to classification of sectors with respect to pollution intensity made by Demirel and Kesidou [57] into highly polluting sectors (food products and beverages, chemicals and chemical products, basic metals and metal products, non-metallic and mineral products, electricity production and supply and environmental protection) and moderately polluting sectors (wood and paper products, textiles, machinery and equipment, electrical machinery and apparatus, motor vehicles and transportation and others). In addition, since the export orientation might influence implementation of proactive environmental strategy [58,59] and eco-innovation [60], the performed analysis has taken into consideration geographical market reach of the surveyed firms-local, regional or national and international.…”
Section: Control Variablesmentioning
confidence: 99%